Resurgence of diphtheria and its outcome among children in western Uttar Pradesh: a battle to conquer - Bhatnagar, Ruchika; Sahai, Lahar (International Journal of Contemporary Pediatrics, 2019)
Background: Considered as a rare clinical entity in immediate post-vaccination era, diphtheria has now started gaining surface in India for last few years, with an epidemiological shift involving older children owing to poor immunization coverage and waning immunity. Thus, it is imperative to quantify disease burden, analyses the clinical profile and factors affecting the outcome of diphtheria in children. Methods: A prospective observational study conducted in the Pediatric department of a teaching hospital where all children admitted with clinical diagnosis of diphtheria during the study period were included. Demographic data and clinically relevant information along with complications and outcome were recorded. Cases were managed as per standard treatment protocol providing intensive care support wherever required. Complications and factors affecting the outcome in all diphtheria cases were analysed. Results: Total 53 children were enrolled into study, and the mean age of study population was 7.55±2 years. Fever, pseudo membrane and throat pain were observed in all the cases. Palatal palsy was the earliest and the commonest complication (60.4%) followed by myocarditis (55%). Case fatality rate was 33.9% and myocarditis (77%) was the commonest complication attributing to it. Poor immunization status, late presentation and delayed ADS administration were associated with increased complication rate and unfavorable outcome. Conclusions: Robust immunization activity coupled with improved case-based surveillance would go a long way in preventing further diphtheria outbreaks in community. Sensitization about this re-emerging disease and high index of suspicion in diagnosing it, amongst primary care physicians and peripheral health workers would promote early referral and prompt management thereby reducing morbidity and high mortality associated with diphtheria.